2001
DOI: 10.1073/pnas.012608999
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary adenylate cyclase-activating polypeptide is a sympathoadrenal neurotransmitter involved in catecholamine regulation and glucohomeostasis

Abstract: The adrenal gland is important for homeostatic responses to metabolic stress: hypoglycemia stimulates the splanchnic nerve, epinephrine is released from adrenomedullary chromaffin cells, and compensatory glucogenesis ensues. Acetylcholine is the primary neurotransmitter mediating catecholamine secretion from the adrenal medulla. Accumulating evidence suggests that a secretin-related neuropeptide also may function as a transmitter at the adrenomedullary synapse. Costaining with highly specific antibodies agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
244
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(256 citation statements)
references
References 38 publications
(36 reference statements)
11
244
1
Order By: Relevance
“…Previous studies have indicated that PACAP acts as a primary neurotransmitter at the splanchnicadrenal synapse under the stress response (15)(16)(17). Indeed, PACAP-null mice have been shown to not mount a stress response to insulin shock and to perish under this challenge (17). Despite this physiologically important role, relatively little is known of how PACAP stimulation elicits the initial catecholamine burst under acute sympathetic stimulation.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous studies have indicated that PACAP acts as a primary neurotransmitter at the splanchnicadrenal synapse under the stress response (15)(16)(17). Indeed, PACAP-null mice have been shown to not mount a stress response to insulin shock and to perish under this challenge (17). Despite this physiologically important role, relatively little is known of how PACAP stimulation elicits the initial catecholamine burst under acute sympathetic stimulation.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, chromaffin cells form a critical element of the acute sympathetic stress response. Previous studies have indicated that PACAP acts as a primary neurotransmitter at the splanchnicadrenal synapse under the stress response (15)(16)(17). Indeed, PACAP-null mice have been shown to not mount a stress response to insulin shock and to perish under this challenge (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems reasonable that an autocrine loop would likely promote the rate of neurite extension; potentially, asymmetric inhibition of autocrine PACAP-PAC1 interactions at the growth cone could also influence the direction of growth cone extension. Finally, local PACAP-PAC1 interaction at synapses (Otto et al, 1999(Otto et al, , 2001Roberto and Brunelli, 2000;Hamelink et al, 2002) could be involved in the final stages of guidance or in structural plasticity (i.e., new neurite sprouts could be elicited and attracted to establish more connections). The possible effects of PACAP on growth cone guidance and other aspects of development will undoubtedly provide interesting avenues for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic animals used in this study were wild type and PACAP knock-out C57BL/6 mice generated as previously reported [10]. PACAP-deficient mice were obtained from mixed strain C57BL/6 × 129/SvJ mice backcrossed onto the C57BL/6 background for seven generations.…”
Section: Animalsmentioning
confidence: 99%